Assessment of Soft Tissue Changes by Cephalometry and Two-Dimensional Photogrammetry in Bilateral Sagittal Split Ramus Osteotomy Cases - Jan Rustemeyer; Alice Martin (eJournal of Oral Maxillofacial Research, 2011)
Objectives: We aimed to compare the standard methods of cephalometry and two-dimensional photogrammetry, to evaluate the reliability and accuracy of both methods.Material and Methods: Twenty-six patients (mean age 25.5, standard deviation (SD) 5.2 years) with Class II relationship and 23 patients with Class III relationship (mean age 26.4, SD 4.7 years) who had undergone bilateral sagittal split ramus osteotomy were selected, with a median follow-up of 8 months between pre- and postsurgical evaluation. Pre- and postsurgical cephalograms and lateral photograms were traced and changes were recorded.Results: Pre- and postsurgical measurements of hard tissue angles and distances revealed higher correlations with cephalometrically performed soft tissue measurements of facial convexity (Class II: N-PG, r = - 0.50, P = 0.047; Class III: ANB, r = 0.73, P = 0.005; NaPg , r = 0.71, P = 0.007;) and labiomental angle (Class II: SNB, r = 0.72, P = 0.002; ANB, r = - 0.72, P = 0.002; N-B, r = - 0.68, P = 0.004; ANS-Gn, r = 0.71, P = 0.002; Class III: ANS-Gn, r = 0.65, P = 0.043) compared with two-dimensional photogrammetry. However, two-dimensional photogrammetry revealed higher correlation between lower lip length and cephalometrically assessed angular hard tissue changes (Class II: SNB, r = 0.98, P = 0.007; N-B, r = 0.89, P = 0.037; N-Pg, r = 0.90, P = 0.033; Class III: SNB, r = - 0.54, P = 0.060; NAPg, r = - 0.65, P = 0.041; N-Pg, r = 0.58, P = 0.039).Conclusions: Our findings suggest that cephalometry and two-dimensional photogrammetry offer the possibility to complement one another.